Phenology and repproduction of the coffee borer (Hypothenemus hampei Ferrari) during the fruit growth. - Camilo, José Efraín (2003)
The study was conducted in La Cumbre, Santiago,Dominican Republic (2000-2001 crop) to determine thepositioning stage and the number of stages of the coffee beanborer, during the fruit growth. It consisted of systematicweekly samplings, starting at 77 days after the primaryblooming (DAPB). It consisted of four replication, 25 fruitswere collected from each replication (five fruits per branchfrom five plants). It was observed that from 70 up to 86 % ofthe bean borers that migrated, remained in the positioningstage B (susceptible to the handling tools) before the 112DAPB. From this date on, a marked decreased was found inthe number of bean borers as the fruit age increased, until itleveled off at 10 % after the 147 DAPB. On the other hand,the borers. percentage the positioning stage D (initiatingbreeding) increased from 2 to 57 %. The number of eggs andlarvae increased after the 112 DAPB, from 23 eggs and fourlarvae up to 286 and 396, respectively, for every 100 coffeebeans, observing at this time the largest damage in theimmature stages of the cotyledons. An increased from nine to108 pupae was observed for every 100 fruits, after the 119 upto 189 DAPB.